State of the Art Detection System for Curcumin Analog - Hannah Jebarani, Angelene; Prakash Francis, Arul; Devasena, Thiyagarajan (Current Drug Discovery Technologies, 2015)
In spite of the need for sensing bisdemethoxycurcumin analog (BDMCA), there is no detection system available so far. For the first time, we have demonstrated a sensing system for detecting BDMCA. Initially, chitosan thin films of three different molecular weights (low, average, high) were tested for the conductivity. The high molecular weight chitosan film was found to produce higher conductance and hence, used as the substrate. Addition of BDMCA to this substrate induced a significant conductance change (as revealed by impedance analyzer), making the detection system qualitative. Addition of increasing concentrations of BDMCA produced significantly concomitant increase in the conductivity (observed as decrease in current density as revealed by cyclic voltammetry) making the sensor quantitative. Our results show that this chitosan based electrochemical sensing system can be used for the rapid quantitative detection of BDMCA. As there is no BDMCA sensor available so far, this type of detection is very essential to monitor the pharmacokinetic behavior, the therapeutic dosage, bioavailability and related toxicity of BDMCA in different formulations and samples.
Keywords: sensing